Majewska, R. (2020) Tursiocola neliana sp. nov (Bacillariophyceae) epizoic on South African leatherback sea turtles (Dermochelys coriacea) and new observations on the genus Tursiocola. Phytotaxa 453 (1): 1–15. - Majewska, Roksana (Phytotaxa, 2020)
N/A